1973 International Microelectronic Symposium : [proceedings] - Mandel, Robert (International Society for Hybrid Microelectronics, Inc., 1973)
Dangerous is a dynamite mix of breathtaking romance and danger set among the magnificent ballrooms and country houses of Regency England. The impetuous Prudence knew the risks a woman took by visiting a gentleman in the dead of night. ... Amanda Quick is the pseudonym for Jayne Anne Krentz.